LC-MS/MS analysis and antioxidant activity of ethanol fraction of Aglaonema modestum leaves - SARONOM SILABAN; BAJOKA NAINGGOLAN; JUANDI IKHWAN; NUR HARLIANANDA; MURNIATY SIMORANGKIR (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Silaban S, Nainggolan B, Ikhwan J, Harliananda N, Simorangkir M. 2024. LC-MS/MS analysis and antioxidant activity of ethanol fraction of Aglaonema modestum leaves. Biodiversitas 25: 4756-4762. Free radicals are one of the triggers of various diseases. Excessive free radicals have the potential to cause oxidative stress, such as diabetes, heart disease, Alzheimer's, and Parkinson's disease. Antioxidants can be used to prevent free radicals. Synthetic antioxidants have unnecessary side effects, and natural antioxidants can be a safer alternative. Natural antioxidants can come from plants, which contain phenolic compounds in the form of flavonoids. Aglaonema modestum, with the local name simargaolgaol, contains this compound. This plant is often found in Barus, North Sumatra, Indonesia, and is usually used by the community as traditional medicine for internal and external wounds. This study aims to identify the potential antioxidant activity of the leaves ethanol fractions of A. modestum. Purification was done using the standard column chromatography method, antioxidant activity analysis using the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method with vitamin C as a control, and fraction compound analysis using LC-MS/MS. Antioxidant activity value (IC50) of ethanol fraction of A. modestum consecutively at 30.953 ppm (very strong), 109.809 ppm (moderate), and vitamin C with an IC50 value of 2.304 ppm (very strong). The results of LC-MS/MS analysis of the ethanol fraction identified three compounds, namely Cadsurenin K (RT 5.91 minutes), Methyl ophiopogonone B (RT 6.37 minutes), and Schizandrin C (RT 7.30 minutes). The ethanol fraction of A. modestum leaves has alternative potential as a natural antioxidant.